Green Innovation: Harmonizing Creative Art Literacy and Upcycling for Sustainable Community Development: Green Innovation: Harmonizing Creative Art Literacy and Upcycling for Sustainable Community Development - Liena Prajogi; Yulita Fairina Susanti; Wiwiek Mardawiyah Daryanto (Institut IPMI, 2026)
The global environmental crisis, marked by escalating plastic waste and climate instability, demands a transition from linear consumption to a restorative circular economy. This paper analyzes the